History and further tasks of the development of the UNESCO program «Man and the Biosphere» and biosphere reserves network in Russia - V. M. Neronov; A. A. Lushchekina (Проблемы постсоветского пространства, 2018)
The review describes the subject of the UNESCO Man and the Biosphere (MAB) program and how the network of Russian biosphere reserves was developed. The MAB Program is designed to coordinate the efforts of scientists from many countries who conduct fundamental research in order to reduce anthropogenic impact and the gap between consumption and conservation. Tendencies of population growth and migration, growing demands for energy and natural resources, globalization of the economy, centralization of management, the difficulty of access to necessary information — all these factors have a direct or indirect impact on the environment, and hence on the prospects for human survival and development. According to UNESCO official documents biosphere reserves are protected zones of a representative terrestrial and coastal environment that have gained international recognition because of their importance for nature protection, scientific knowledge and skills, and the preservation of human values for sustainable development. To date, the World Network of Biosphere Reserves includes 686 such protected areas in 122 countries, including 20 transboundary ones.